2020
DOI: 10.1111/jfpp.14884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation method on physicochemical, scavenging, and proliferative properties of gelatin from Yak skin

Abstract: Gelatin as a high molecular weight protein and has been extensively applied in diverse fields, such as food, cosmetics, pharmaceuticals, and photography, in which it acts as a thickener, stabilizer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For Nile tilapia skins and Nile perch skins, the WHC values are 6.4 g/g and 6.9 g/g, respectively [ 45 ]; several of our gelatins approach these values. Gelatins prepared from yak skins showed very low WHC values; depending on the preparation and drying conditions it was 0.40–0.47 g/g, which are relatively low values compared to our gelatins [ 50 ]. In our previous study on the preparation and characterization of chicken skin gelatins, we found WHC 3.85–5.58 g/g, depending on extraction conditions [ 51 ], which are almost the same values as for our highest-quality fish gelatins.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For Nile tilapia skins and Nile perch skins, the WHC values are 6.4 g/g and 6.9 g/g, respectively [ 45 ]; several of our gelatins approach these values. Gelatins prepared from yak skins showed very low WHC values; depending on the preparation and drying conditions it was 0.40–0.47 g/g, which are relatively low values compared to our gelatins [ 50 ]. In our previous study on the preparation and characterization of chicken skin gelatins, we found WHC 3.85–5.58 g/g, depending on extraction conditions [ 51 ], which are almost the same values as for our highest-quality fish gelatins.…”
Section: Discussionmentioning
confidence: 97%
“…For Nile tilapia skins and Nile perch skins, the FBC values are 4.7 g/g and 3.6 g/g [ 45 ], which are values comparable to our gelatins. Gelatins prepared from yak skins showed very low FBC values; depending on the preparation and drying conditions it was 0.16–0.20 g/g [ 50 ]. In our aforementioned study on chicken skin gelatins, FBC was very low (0.97–1.26 g/g) compared to fish gelatin, while commercial porcine (260 Bloom) and bovine gelatins (260 Bloom) did not differ significantly (0.42 g/g and 0.71 g/g) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze-dried enzymatic hydrolyzed gelatin is a suitable raw material for preparing gelatin with enhanced biological activity. 18 The hydrolysis and structural characteristics of YSG hydrolysis suggest that YSG subjected to moderate ultrasound (5 min) has great potential as an antioxidant. 19 However, there are few reports on other functional activities of YSG.…”
Section: Introductionmentioning
confidence: 99%